2023
DOI: 10.21542/gcsp.2023.20
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and heart: A reality check

Jayesh Valecha,
Harshwardhan Khandait,
Anagha SK
et al.

Abstract: Migraine is a common neurological disorder affecting 12% of the global population. The common risk factors are adolescent age, genetics, and female sex, and are triggered by hormonal fluctuations, emotional stress, sensory overload, weather changes, alcohol consumption, fasting, cheese, chocolate, smoked fish, yeast extract, cured meats, artificial sweeteners, food preservatives containing nitrates and nitrites, and sleep disturbances. Migraine with aura is associated with an increased risk of cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The occurrence of migraines with or without aura may vary depending on the type of arthritis. Notably, a diagnosis of migraines with aura is limited due to its association with an increased risk of various comorbidities, including ischemic stroke, Parkinson’s disease, bipolar disorder, panic disorder, restless legs syndrome, and patent foramen ovale [ 16 , 35 , 36 ]. The influence of comorbidity in the occurrence of migraines without aura is significantly lower than in migraines with aura [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of migraines with or without aura may vary depending on the type of arthritis. Notably, a diagnosis of migraines with aura is limited due to its association with an increased risk of various comorbidities, including ischemic stroke, Parkinson’s disease, bipolar disorder, panic disorder, restless legs syndrome, and patent foramen ovale [ 16 , 35 , 36 ]. The influence of comorbidity in the occurrence of migraines without aura is significantly lower than in migraines with aura [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A different application of AI is not related to the diagnosis of migraine itself but to the detection of its comorbidities. The relationship between migraine and a higher cardiovascular risk is long known, and it is particularly described for MwA [35]. One of the reasons may be found in the increased risk of subclinical atrial fibrillation (AF) that has been demonstrated in a large cohort of MwA patients with an AI-ECG algorithm [36].…”
Section: Improving Diagnosismentioning
confidence: 99%